ANALISIS PENGARUH PERPUTARAN MODAL KERJA, LIKUIDITAS, STRUKTUR MODAL, SALES GROWTH, STRUKTUR AKTIVA, SIZE TERHADAP PROFITABILITAS (Studi pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia tahun 2012-2016) - Rahmawati, Irna; Mahfudz, Mohammad Kholiq (Faculty of Economics and Business Diponegoro University, 2018)
The purpose of this research is to analyze the effect of working capital turnover, liquidity, capital structure, sales growth, asset structure, size on profitability (ROA) in Manufacturing companies.The population of this research is a Manufacturing company listed on the Indonesia Stock Exchange (BEI) in 2012-2016. The sampling method used is purposive sampling and acquired 25 companies in the sample. The analytical method used is multiple regression analysis and using classical assumption test.Based on the results of research conducted, simultaneous working capital turnover (WCT), liquidity (CR), capital structure (DER), sales growth, asset structure, size effect on profitability (ROA). Then partially, Working Capital Turnover (WCT) has significant negative effect on profitability (ROA), Liquidity (CR) has insignificant negatif effect on profitabilty (ROA), Capital Structure (DER) has significant negative effect on profitabilty (ROA), Sales Growth has insignificant positive effect on profitabilty (ROA), Asset Structure has insignificant positive effect on profitabilty (ROA), Size has significant positive effect on profitabilty (ROA).